THE APPLICATION OF RESTORATIVE JUSTICE AS A LEGAL GOAL (JUSTICE, UTILITY, CERTAINTY) IN THE JURISDICTION OF THE CENTRAL JAVA HIGH PROSECUTOR'S OFFICE - Nikolas, Dwinanda Linchia Levi Heningdyah (UNIVERSITAS PAKUAN, 2025)
This paper aims to provide an understanding of the application of restorative justice as a legal goal (justice, utility, certainty) in the jurisdiction of the Central Java High Prosecutor's Office. Ideally, law enforcers in enforcing the law must be able to realize three (3) basic values of the law, or often referred to as legal goals, namely justice, usefulness, and certainty for the community. As for the stipulation of the Prosecutor's Regulation of the Republic of Indonesia Number 15 of 2020 concerning the Termination of Prosecution Based on Restorative Justice, it is hoped that it will be able to provide justice, usefulness and legal certainty for the community, especially for those who are in legal proceedings